Communication Skills of Vocational College Students After Completing Industrial Training - MD SOPI, NUR AFIZA; Othman, Hasyamuddin (Research and Innovation in Technical and Vocational Education and Training, 2024)
Educational institutions must prioritize the development of employability skills among TVET students, as employers increasingly seek candidates who possess strong employability skills in addition to technical expertise. Hence, this study aims to identify the employability skills of Diploma in Construction Technology students from vocational colleges in the East Coast region, as perceived by both the students and construction industry practitioners, with a focus on communication skills following the completion of industrial training. This study is a quantitative research project supported by qualitative methods using surveys and interviews. Questionnaires were the primary instrument, while interviews served as a supplementary tool. The study included 94 Diploma in Construction Technology students from vocational colleges across the East Coast who had completed their industrial training, as well as three construction industry practitioners involved in the industrial training program, who participated as interviewees. The researcher employed IBM SPSS version 27 software to analyze the quantitative data and conducted thematic analysis for the qualitative data. The findings indicated that the communication skills of Diploma in Construction Technology students from vocational colleges along the East Coast were rated as highly proficient based on the mean score results, as perceived by both the students and construction industry practitioners. Therefore, it is hoped that these students can further develop their communication skills to ensure readiness for job interviews after graduation. This is particularly important considering the increasingly challenging nature of the workforce.